Simulated safety analysis of a total loss of feedwater accident in the steam generator of CPR1000 nuclear power plant - Wang, Guanyi; Zheng, Chaoying; Zhang, Yang; Wu, Peng; Chen, Fangqiang (Frontiers in Energy Research, 2024)
As M310 series units, CPR1000 Nuclear Power Plant in China is also the first batch of demonstration nuclear power plants in China to try out SOP(the state-oriented procedure) accident procedures. The establishment of SOP accident regulations is an important work to mitigate the consequences of radioactive accidents in the design of nuclear power plants, and it is also the embodiment of the defense-in-depth requirements in the implementation of nuclear safety regulations. It can handle superimposed accidents, human errors in program implementation and events not considered in the primary cause sequence. In order to study the efficiency of its upgraded SOP procedure and its ability to deal with severe accidents, the typical primary cause event of severe accidents in nuclear power plantssuch as the total loss of feedwater accident of steam generators has been adopted for research. The initial state of the simulation is the full power operation of the nuclear power plant, the simulation process is from the loss of all the water supply accidents to the whole accident processing. A total of 30 simulation experiments were carried out. The temperature and pressure of the key parameters obtained are the average values of 30 simulation experiments. The stability and efficiency of the updated SOP are evaluated by the treatment time of the water supply loss accident and the changes of reactor temperature and pressure after the accident. The results show that the upgraded SOP procedure is more stable and efficient. The upgraded SOP procedure, when dealing with other types of accidents, has improved the treatment of residual heat conduction in the core, increased the efficiency of accident treatment, and enhanced the safety of the reactor. At the same time, based on the weaknesses of the upgraded SOP procedure, constructive suggestions on changing the setting value of the steam generator bypass valve have also been put forward accordingly. Furthermore, it can be concluded from many simulated accidents that this change will win about 5% more of the disposal time for nuclear power plants under accidents, which provides references for the subsequent upgrading of M310 series power plant procedures.